KAJIAN EKSPERIMENTAL GAS CLEANER YANG DIMODIFIKASI UNTUK MENGEKSTRAK TAR DALAM PRODUCER GAS - Candra Aditia Agustian; Indra Mamad Gandidi; Harmen Burhanuddin (Jurnal Ilmiah Teknik Mesin, 2013)
Producer gas from biomass gasification consists of tar from pyrolysis process which is notdegradation thermal well before out from the reactor. In fact tar is a serious problem that must beconsidered in the process of gasification, especially for an internal combustion engineapplication.Gas cleaning system is one the methods to reduce the tarproduced in gasificationprocess. The research purpose which is to design a purify device for the producer gas which isintegrated and also to know the influence of gas speed and water debit towards tar getting asmeasurement research of IGCS. The research does by using reactor with diameter dimension 0,8 mand 1,5 m high. The result of this research getting the gas speed for the cyclone about 2,4 m/s andflow of water in venturi scrubber 3,3 l/min, collected tar is 12 gram with 66,67 % cyclone efficiencyand 10 gram with 44,44 % venturi scrubber efficiency. Meanwhile, rotary separator gas speedabout 2,6 m/s, it is able to reduce 10 gram tar with 55,56 % efficiency. The result from combinetesting show that the tar left in producer gas is only 210 mg/m3 with 94,4 % efficiency.Keywords : Gasifikasi Biomassa, Gascleaning, IGCS, Tar